Exploring line managers' perspectives on using data in managing sickness absence: a qualitative study - Lene Rasmussen; Maj Britt Dahl Nielsen; Anne Helene Garde; Jesper Kristiansen (BMC, 2024)
Abstract Purpose The purpose of this study is to explore line managers' perspectives on data as tool in the management of sickness absence in public sector workplaces in Denmark. Methods The study is a qualitative study based on 19 semi-structured interviews with line managers from four public sector workplaces characterized by high levels of sickness absence or poor work environment. The interviews were analysed inductively using thematic analysis. Results The findings show that line managers primarily use data to identify employees at risk of sickness absence. The experiences highlighted related to how and when data are perceived as a valuable tool by the line managers, and that nuances in the data, accessibility of the data and how data are presented are important factors to ensure appropriate follow-up on sickness absence. Conclusions The findings suggest that for line managers to use data to manage sickness absence appropriately, the data must be easily accessible, simple for line managers to understand and provide line managers with a sufficient overview of sickness absence in their work units. It is also important to consider other factors affecting sickness absence, such as the work environment, when aiming to reduce sickness absence.